Perlindungan Hukum Bagi Pekerja Anak Di Kota Tangerang - Yoga Alvin Adrian (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
This study aims to provide an overview of the form of legal protection for child labor in the city of Tangerang and the form of policies issued by the Tangerang city government. This study uses a qualitative research method in the form of literature review. The specification used in this research is descriptive analytical, the data used in this research are primary and secondary data. Primary data in this study were interviews with several children who were underage child labor and as secondary data in this study, it was obtained Law Number 13 of 2003 concerning Manpower, Perda Tangerang Number 2 of 2015, and Perwal Tangerang Number 65 of 2016 which related to the writing of this thesis and then the data obtained is compiled with a descriptive method. The results of the study conclude that despite the existence of legal protection and policies provided by the Tangerang city government in dealing with the problem of underage child labor, there are still many employers who commit violations. The results of this study are expected to be able to contribute scientific thinking and add new abilities for researchers as well as add new abilities for researchers as well as provide input to the Tangerang local government, especially as a reference for decision making on the welfare of children who are exploited.Keywords: Legal Protection, minors